Study of the charge transfer process in the polyaniline/graphite heterojunction by conductive atomic force microscopy - N. A. Davletkildeev; E. Yu. Mosur; D. V. Sokolov; I. A. Lobov (Омский научный вестник, 2020)
Thin layers of polyaniline on the surface of highly oriented pyrolytic graphite are obtained by in-situ chemical oxidative polymerization of aniline. The current-voltage characteristics of the tip/polyaniline/graphite contact, which have a form characteristic of tunnel contacts, have been measured by the method of conducting atomic force microscopy. By modeling the current-voltage characteristics using the Simmons model, the width of the potential barrier is determined, which for the investigated heterojunction is 0,5 nm.